IPTEK BAGI PRODUK EKSPOR UKM PENGRAJIN ROTAN “LEU BAGO AWE” - Ully Muzakir (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2017)
The objective of this program is to boost export growth of rattan handicraft products in Aceh Besar regency, namely UKM